Musical Literacy and Jazz Musicians in the 1910s and 1920s - Chevan, David (Current Musicology, 2001)
In 1988, I conducted a telephone interview with the African American New Orleans clarinet player Willie James Humphrey about his tenure from 1925 to 1932 in the riverboat band led by Fate Marable. During our conversation, I asked Humphrey if Marable had hired him because of his skills as a jazz musician. Although we were talking by phone I could feel the mood of the conversation change. Humphrey sounded irritated as he replied, "You had to be a musician [his emphasis], 'cause that's the only way you could get on there. You had to know how to read."